PENGARUH SMOOTHIES KOMBINASI ANEKA BUAH DAN SAYUR TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL - Widya Aris Anggoro Wati; Mohammad Jaelani; Enik Sulistyowati (Poltekkes Kemenkes Semarang, 2019)
Background : People with hypercholesterolemia used pharmacological therapies such as fibrates, statins, nicotinic acid and bile acids. Side effects of these drugs can cause other diseases, beside that the treatment of hypercholesterolemia takes a long time and many of them are not compliant therefore other alternative treatment are needed by increasing the consumption of fruits and vegetables.Objective : This study aimed to know the effect of giving smoothies combination of various fruits and vegetables to lower of total cholesterol level in adult woman.Method : This research is true experiment study with Randomized Pre and Post Test Control Group Design design. Sampling was done randomly to get 17 treatment samples and 17 control samples. Intervention was given by of giving smoothies combination of various fruits and vegetables for 21 days. Bivariate test used independent t-test, while multivariate used anova repeated measured.Result: The result showed that intervention of combination fruits and vegetables for 21 days showed significant differences in total cholesterol levels between treatment groups and intervention groups before and after intervention (p = 0.01) by 33 mg / dl decrease level. There is an effect of giving smoothies combination of various fruits and vegetables to decrease total cholesterol level (p = 0.021). Fiber intake (p = 0.011) and carbohydrate intake (p = 0.019) also had an effect on lowering total cholesterol levels.Conclusion : The conclusion showed that smoothies combination of various fruits and vegetables for 21 days can reduce total cholesterol levels by 33 mg/dl.